2020
DOI: 10.3390/antiox9020174
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sirt3 in Differential Sex-Related Responses to a High-Fat Diet in Mice

Abstract: Metabolic homeostasis is differently regulated in males and females. Little is known about the mitochondrial Sirtuin 3 (Sirt3) protein in the context of sex-related differences in the development of metabolic dysregulation. To test our hypothesis that the role of Sirt3 in response to a high-fat diet (HFD) is sex-related, we measured metabolic, antioxidative, and mitochondrial parameters in the liver of Sirt3 wild-type (WT) and knockout (KO) mice of both sexes fed with a standard or HFD for ten weeks. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Fasting glucose level remained unchanged by either ovx or Sirt3 depletion in both SFD and HFD-fed mice ( Figure 2 A). In agreement with our previous observations [ 13 ], we found no change in body weight in SFD- and HFD-fed sham mice (data not shown). However, body weight gain was affected differently in ovx KO mice, depending on type of diet: SFD-fed KO ovx mice gained less weight than WT ovx ( a p < 0.05) or sham KO mice (** p < 0.01) ( Figure 2 B).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Fasting glucose level remained unchanged by either ovx or Sirt3 depletion in both SFD and HFD-fed mice ( Figure 2 A). In agreement with our previous observations [ 13 ], we found no change in body weight in SFD- and HFD-fed sham mice (data not shown). However, body weight gain was affected differently in ovx KO mice, depending on type of diet: SFD-fed KO ovx mice gained less weight than WT ovx ( a p < 0.05) or sham KO mice (** p < 0.01) ( Figure 2 B).…”
Section: Resultssupporting
confidence: 94%
“…It promotes mitochondrial oxidative metabolism via deacetylation of numerous metabolic enzymes, including those involved in FA catabolism, as demonstrated earlier by an abnormal accumulation of FA oxidation intermediates in Sirt3 KO mice [ 4 ]. It was also shown that Sirt3 expression is reduced during chronic HFD in male mice [ 4 , 13 ]. Although E2-dependent protection includes improvement of mitochondrial function [ 14 ], it is not clear whether Sirt3, as a pivotal factor regulating mitochondrial biogenesis and reactive oxygen species (ROS) management, participates in these events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, SIRT3 deficiency resulted in triglyceride accumulation in the liver. However, an HFD reduces only SIRT3 levels in males [ 361 ]. Contrarily, modulation of the SIRT3/FOXO1 pathway through salvianolic acid B was shown to improve NAFLD in rats, by reducing oxidative stress [ 362 ].…”
Section: The Role Of Sirtuins In Metabolic Tissuesmentioning
confidence: 99%
“…In most mammals, females show lower incidence of some age-related pathologies linked with oxidative stress conditions, and this sex difference disappears after menopause, which led to the conclusion that this protection is attributed to the effect of sex hormones [ 28 ]. By conducting in vivo experiments on Sirt3 wild-type (WT) and knockout (KO) mice of both sexes fed with a standard or high-fat diet (HFD) for ten weeks, Pinterić et al [ 29 ] found significant sex differences in male and female mice responses at the metabolic level, oxidant/antioxidant status, and liver mitochondrial parameters. Their study points towards a different role of SIRT3 in males and females under the conditions of nutritive stress.…”
mentioning
confidence: 99%